1975
DOI: 10.1159/000245562
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm of Plasma Cortisol in the Aged (Cosinor Method)

Abstract: Plasma cortisol circadian rhythm was investigated in 18 apparently healthy elderly subjects, in 11 elderly patients affected by cerebrovascular hemiplegia and in 11 otherwise healthy blind elderly subjects. Results were microscopically analyzed by the least squares and Cosinor methods. The circadian rhythm of plasma cortisol was present and normal both in elderly subjects and in elderly patients with cerebrovascular hemiplegia. By contrast, a plasma cortisol rhythm was not found in blind elderly subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Although we did not observe elevations in plasma CORT in aged rats, we demonstrated modest, but significant, elevations in hippocampal CORT, lasting only throughout the inactive phase. Plasma CORT levels were comparable between young and aged rats throughout the inactive phase, while levels were blunted throughout the active phase in the aged rats, as has been established previously in aged humans and rodents (Colucci, et al, 1975, Hauger, et al, 1994, Milcu, et al, 1978). The discrepancy between the plasma CORT data reported here and that of some, but not other studies (Sapolsky, 1992) may be explained by the unique use of an automated serial blood sampling technique here, whereby rats were not handled at all during a sampling period that extended across the entire day.…”
Section: Discussionsupporting
confidence: 82%
“…Although we did not observe elevations in plasma CORT in aged rats, we demonstrated modest, but significant, elevations in hippocampal CORT, lasting only throughout the inactive phase. Plasma CORT levels were comparable between young and aged rats throughout the inactive phase, while levels were blunted throughout the active phase in the aged rats, as has been established previously in aged humans and rodents (Colucci, et al, 1975, Hauger, et al, 1994, Milcu, et al, 1978). The discrepancy between the plasma CORT data reported here and that of some, but not other studies (Sapolsky, 1992) may be explained by the unique use of an automated serial blood sampling technique here, whereby rats were not handled at all during a sampling period that extended across the entire day.…”
Section: Discussionsupporting
confidence: 82%
“…Circadian rhythms also appear to remain generally unchanged with age for ACTH (113,123) and cortisol (113,115,117,(123)(124)(125)(126)(127)(128)(129). Trends have been reported, however, showing higher evening (111,130) or morning (128) cortisol levels at older ages; higher 24-h mean cortisol concentrations at older ages have also been reported (122,129) although others have not found such differences by age (123,131).…”
Section: B Nonstimulated Hpa Functionmentioning
confidence: 96%
“…The change in phase was thought to be a possible result of sleep disturbance in old age. In other studies, Montalbetti and colleagues found that the Cortisol rhythm was normal in the healthy elderly and in elderly patients with cerebrovascular hemiplegia, but abnormal in the elderly blind 53,60 . It seems probable that growth hormone secretion does not occur with a true circadian rhythm, but passively follows the appearance of Stage 3 and Stage 4 sleep (slow‐wave sleep); and both slow‐wave sleep and growth hormone secretion are minimal in the elderly 31,59,83 .…”
Section: Biologic Rhythms and Sleep/wake Function In The Agedmentioning
confidence: 98%